Evaluating Skills, Self-Efficacy, and Willingness for CPR in Rural Junior High Students: A Comparison of HEART Film and BEAT Module - Wahyu Wulansari, Yunita; Wirasakti, Guruh; Darotin, Rida; Madyaning Nastiti, Eky; Ekaprasetia, Feri (Jurnal Kesehatan dr. Soebandi, 2025)
The high incidence of cardiac arrest, coupled with the low number of bystanders performing CPR as the first responders in out-of-hospital cases, continues to draw attention worldwide. The HEART film and BEAT module present viable media solutions in efforts to provide CPR training to various community groups. The purpose is to analyze the differences between the HEART film and the BEAT module in relation to skills, self-efficacy and willingness of school-age students in conducting CPR in rural areas. This study utilized a quasi-experimental method with a two-group pretest-posttest design, conducted on 144 samples divided into two groups: the HEART film (Helping Emergency Actions Resuscitate Today) group and the BEAT module (Bringing Emergency Actions to Thrive) group. Simple random sampling was used to select participants from SMPN 1 Kalisat. In the pretest phase, no significant differences were found in skills, self-efficacy, and willingness between the HEART and BEAT groups (p > 0,05). However, after training and one week post-training, significant differences were observed in these factors (p < 0,05). The HEART film-based CPR learning media has proven to be more effective than the BEAT module in enhancing students' skills, self-efficacy, and willingness. However, both learning media can be considered suitable and effective for CPR education among students in rural areas..